2006
DOI: 10.1093/nar/gkl668
|View full text |Cite
|
Sign up to set email alerts
|

Collision events between RNA polymerases in convergent transcription studied by atomic force microscopy

Abstract: Atomic force microscopy (AFM) has been used to image, at single molecule resolution, transcription events by Escherichia coli RNA polymerase (RNAP) on a linear DNA template with two convergently aligned λpr promoters. For the first time experimentally, the outcome of collision events during convergent transcription by two identical RNAP has been studied. Measurement of the positions of the RNAP on the DNA, allows distinction of open promoter complexes (OPCs) and elongating complexes (EC) and collided complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 40 publications
5
99
0
Order By: Relevance
“…Our results are consistent with the transcriptional collision model that has been proposed following the analyses of adjacent transcripts and cis -NATs in yeast (Puig et al 1999;Prescott and Proudfoot 2002) and the observation of the collision of RNA polymerases by atomic force microscopy (Crampton et al 2006). RNA polymerases bind to the upstream regions of genes and synthesize mRNAs, moving toward the 39-ends of the genes.…”
Section: à15supporting
confidence: 91%
See 1 more Smart Citation
“…Our results are consistent with the transcriptional collision model that has been proposed following the analyses of adjacent transcripts and cis -NATs in yeast (Puig et al 1999;Prescott and Proudfoot 2002) and the observation of the collision of RNA polymerases by atomic force microscopy (Crampton et al 2006). RNA polymerases bind to the upstream regions of genes and synthesize mRNAs, moving toward the 39-ends of the genes.…”
Section: à15supporting
confidence: 91%
“…This suggested that RNA polymerases did not stop at the terminator of the upstream transcript and affected the transcription of the downstream transcript. Recently, the collision of Escherichia coli RNA polymerases was observed by atomic force microscopy (Crampton et al 2006). This observation showed that RNA polymerases do not pass each other or displace one another, but instead stall against each other.…”
mentioning
confidence: 99%
“…Second, antisense mRNAs were suggested to promote the methylation of sense mRNA promoters. And third, the formation of double-stranded RNA hybrids may interfere with further mRNA processing (Wutz et al, 1997;Lai, 2002;Prescott and Proudfoot, 2002;Tufarelli et al, 2003;Lavorgna et al, 2004;Crampton et al, 2006). These models are not mutually exclusive, and more than one of them may apply to the situation of p53 and WRAP53.…”
Section: Discussionmentioning
confidence: 99%
“…While this phenomenon has been observed in bacteria (Crampton et al 2006) and budding yeast (Prescott and Proudfoot 2002), none has been reported in mammals. However, computational analyses of genes with NATs have found an anticorrelation between the length of overlap and the expression levels of SAS pairs (i.e., the greater the overlap is, the lower the expression of either transcript) (Osato et al 2007), consistent with a transcriptional collision model in which convergent transcripts sterically hinder transcription of one another.…”
Section: Transcript or Act Of Transcription?mentioning
confidence: 92%